2015
DOI: 10.1074/jbc.m115.643577
|View full text |Cite
|
Sign up to set email alerts
|

Prion-Protein-interacting Amyloid-β Oligomers of High Molecular Weight Are Tightly Correlated with Memory Impairment in Multiple Alzheimer Mouse Models

Abstract: Background: Amyloid-␤ (A␤) oligomers are key in Alzheimer disease (AD) but are diverse and poorly characterized. Results: Multiple A␤ forms were measured across the life span of AD model mice and human AD brain. Conclusion: A␤ species interacting with prion protein were tightly linked to behavioral impairment. Significance: An A␤ oligomer subset with defined biochemical properties is present in multiple AD-relevant samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
135
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 88 publications
6
135
0
Order By: Relevance
“…To investigate whether the SAM could ameliorate behavioral deficits of aged APP/PS1 transgenic mice (Jankowsky et al, 2003, 2004), we assessed their behavior in multiple behavioral paradigms after 4 weeks of treatment with the SAM or vehicle. Because this mouse strain develops behavioral deficits starting at 6 months of age, when Aβo levels rise (Gimbel et al, 2010; Kostylev et al, 2015; Park et al, 2006), their deficits were well-established when SAM treatment started at an average age of 14 months (Figure S2). First, mice were subjected to novel object recognition testing (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether the SAM could ameliorate behavioral deficits of aged APP/PS1 transgenic mice (Jankowsky et al, 2003, 2004), we assessed their behavior in multiple behavioral paradigms after 4 weeks of treatment with the SAM or vehicle. Because this mouse strain develops behavioral deficits starting at 6 months of age, when Aβo levels rise (Gimbel et al, 2010; Kostylev et al, 2015; Park et al, 2006), their deficits were well-established when SAM treatment started at an average age of 14 months (Figure S2). First, mice were subjected to novel object recognition testing (Figure 4A).…”
Section: Resultsmentioning
confidence: 99%
“…Kostylev and colleagues used a PrP C -ELISA (PLISA) to quantify the Aβo-PrP C interaction in brain tissue from several mouse models of AD and also healthy and AD human brain [9, 21]. This study found that PrP C interacting Aβo are highly correlated with learning and memory deficits in multiple mouse models of AD as defined by PLISA activity [21]. Furthermore, PLISA activity disappeared with PrP C mediated depletion of high-molecular weight Aβo from mouse of the varying mouse models.…”
Section: Cellular Prion Protein (Prpc) As a Receptor For Aβomentioning
confidence: 99%
“…In vitro, exposure of soluble Aβ oligomers results in rapid blockage of long-term potentiation and binding to cellular prion protein, interfering with normal synaptic function [3,13,14,15]. Moreover, soluble Aβ oligomers may cause tau hyperphosphorylation and neuronal degeneration in hippocampal neurons [12,16,17].…”
Section: Introductionmentioning
confidence: 99%